A General Method for Fractional-Integer Order Systems Synchronization - Hannachi, Fareh (Journal of Applied Nonlinear Dynamics, 2026)
This paper investigates different type of synchronization between fractional-order (chaotic, hyperchaotic) systems and integer-order (chaotic, hyperchaotic) systems. Based on the idea of the decomposition of the controller in the response system in two sub-controllers and the stability theory of the linear integer-order system, we design the effective controller to realize the synchronization, Antisynchronization, function projective synchronization, inverse function projective synchronization between fractional-order and integer-order systems. Finally, the fractional-order L¨u’s system and the Lorenz system of integer order are used to demonstrate the effectiveness of the proposed method with numerical simulation.